2015
DOI: 10.1002/mus.24579
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spinal cord lesion level and severity on H‐reflex excitability and recovery curve

Abstract: The changes in spinal reflexes as measured by the H-reflex and its recovery curve after SCI depend on the severity, but not on the level of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Table 1 ), whereas nine of the patients in the transcutaneous SCS group had motor-incomplete lesions (4 AIS C, 5 AIS D). Previous studies of the soleus H reflex revealed significantly smaller M max amplitudes in individuals with complete compared to incomplete SCI [ 87 ]. As there was no correlation of the H max -to-M max ratio with the severity of SCI [ 87 , 88 ], also the sizes of H max must have been smaller in case of motor-complete lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 ), whereas nine of the patients in the transcutaneous SCS group had motor-incomplete lesions (4 AIS C, 5 AIS D). Previous studies of the soleus H reflex revealed significantly smaller M max amplitudes in individuals with complete compared to incomplete SCI [ 87 ]. As there was no correlation of the H max -to-M max ratio with the severity of SCI [ 87 , 88 ], also the sizes of H max must have been smaller in case of motor-complete lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the soleus H reflex revealed significantly smaller M max amplitudes in individuals with complete compared to incomplete SCI [ 87 ]. As there was no correlation of the H max -to-M max ratio with the severity of SCI [ 87 , 88 ], also the sizes of H max must have been smaller in case of motor-complete lesions. Along this line, earlier studies showed greater soleus stretch reflexes [ 88 ] as well as responses to Achilles’ tendon taps [ 89 ] in motor-incomplete vs. complete SCI that were attributed to differences in long-tract sparing and secondary mechanical adaptations in the muscle and tendon complex associated with different SCI severities [ 87 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homosynaptic depression was assessed by H-reflex recovery curve [ 40 42 ]. We plotted the Hr recovery curve by delivering pairs of stimuli following the same setting described above with equal Hr (max) intensity and duration.…”
Section: Methodsmentioning
confidence: 99%
“…The Hoffman reflex (H-reflex), the electrophysiological equivalent of the spinal stretch reflex, was measured as an analogue of spasticity. Spasticity is associated with hyperreflexia and spasticity severity is known to correlate with higher H-reflex amplitudes particularly with high frequency stimulation (Chen et al, 2001;Garrison et al, 2011;Hoving et al, 2006;Kumru et al, 2015;Pizzi et al, 2005;Ryu et al, 2017;Tekgül et al, 2013;Yates et al, 2008). H-reflexes were elicited in rats lightly sedated with isoflurane (0.5 to 1% v/v in oxygen) such that vibrissae and whisking reflexes were absent.…”
Section: Electrophysiological Assessments and Signal Processingmentioning
confidence: 99%